Association Between Clinical Variables and Dyspnea-Related Fear of Movement in Patients With Chronic Obstructive Pulmonary Disease: A Cross-Sectional Study - Çağla Nur Yetim; Saniye Aydoğan Arslan; Selma Demir (Evaluation & the Health Professions, 2026)
This study aimed to examine the relationship between dyspnea-related fear of movement and clinical variables in patients with Chronic Obstructive Pulmonary Disease (COPD). The cross-sectional study included 59 patients with COPD. Perception of dyspnea (Modified Medical Research Council Dyspnea Scale (mMRC)), functional exercise capacity (6-min walk test (6MWT)), respiratory function (spirometry), maximal inspiratory and expiratory pressures (MIP/MEP- mouth pressure measurement device), quadriceps (QS) muscle strength (digital dynamometer), balance (Mini-Balance Evaluation Systems Test (Mini-BESTest)), and dyspnea-related fear of movement (Breathlessness Beliefs Questionnaire (BBQ)) were assessed. The perception of fear of movement associated with dyspnea was found to be related to mMRC, Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage, spirometry, digital dynamometer, 6MWT and Mini-BESTest ( r = .318- .488, p < .05), but not to MIP, MEP and other clinical variables ( p > .05). Regression analysis showed that fear of movement due to dyspnea explained 9% of the variance in QS muscle strength, 15% in 6MWT distance, and 9% in Mini-BESTest score. Fear of movement due to dyspnea was identified as a clinically relevant factor in COPD patients, with BBQ scores notably higher than those reported in previous studies, and affected QS muscle strength, balance, and functional exercise capacity.